(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the effect of combining sodium bicarbonate with bupivacaine on prolonging peripheral nerve block time.Material and Method: Following the approval of the required Ethics Committee, 24 male New Zealand rabbit (4250-5350 g) were randomized and divided into three groups. Group 1 sham n:8; Group 2 (bupivacaine): 0.5 mL of 0.5% bupivacaine (0.5 mg / kg) injected into the perineural area. n:8; and Group 3 (bupivacaine + sodium bicarbonate): 0.5 ml of 0.5% bupivacaine + sodium bicarbonate (125 ml of 8.4% injected into the perineural area. n: 8. After the skin was closed in all groups, the paw pull response was monitored and recorded every 30 minutes until the sensory block of the experimental animal returned back. Hot-plate test was used for analgesia evaluation. In addition, tissue histopathology was examined for histopathological evaluation of the injection site. Sensory block was evaluated with claw tightening test and claw pull test (hot-plate) response. The measurements were carried out every 30 minutes for 120 minutes or until the block was completely resolved.Results: 30., 60. and 90.min paw pull response in Group 2 and Group 3 showed statistically significant elongation when compared to Group 1, this difference disappeared in 120 minutes. Compared to the sham group, the 30 min hot plate and claw pull response was significantly longer in group 3 (sodium bicarbonate and bupivacaine), this difference disappeared in 60 minutes (p = 0.018).Conclusion: When sodium bicarbonate and bupivacaine are combined, it was seen in this study that the sensory block was prolonged. We believe that the current results can be used as a guide for future studies.